Antiplasmodial activity, biosynthetic gene clusters diversity, and secondary metabolite constituent of selected Indonesian Streptomyces - Ema Damayanti; Puspita Lisdiyanti; Andini Sundowo; Shanti Ratnakomala; Achmad Dinoto; Jaka Widada; Mustofa MUSTOFA (Society for Indonesian Biodiversity, 2021)
Abstract. Damayanti E, Lisdiyanti P, Sundowo A, Ratnakomala S, Dinoto A, Widada J, Mustofa. 2021. Antiplasmodial activity, biosynthetic gene clusters diversity, and secondary metabolite constituent of selected Indonesian Streptomyces. Biodiversitas 22: 3478-3487. Actinobacteria of the genus Streptomyces are known as the primary candidate antibiotics, but still limited for antiplasmodial drugs. This study aimed to investigate the antiplasmodial activity, the biosynthetic gene clusters (BGCs) diversity, and the secondary metabolites constituent of selected Indonesian Streptomyces. The bacteria were isolated from various habitats: karst soil (GMR22), mangrove sediments (BSE7F and SHP 22-7), and marine sediment (GMY01). Molecular identification by 16S rDNA sequencing were performed for confirmation and morphological characterization by scanning electron microscope (SEM) were performed for identification. In vitro antiplasmodial assay was performed on human Plasmodium falciparum FCR-3. The BGCs which encode secondary metabolites were analysed using antiSMASH version 5 based on available whole genome sequence (WGS) data. The secondary metabolites were obtained from liquid fermentation followed by extraction using methanol and ethyl acetate. The secondary metabolites constituent was determined by liquid chromatography tandem mass spectrometry (LC-MS/MS). The molecular identification showed that GMR22 had similarity to Streptomyces lactacystinicus (98.02%), while BSE7F was similar to Streptomyces althioticus (97.06%), SHP 22-7 was similar to Streptomyces rochei (94.84%), and GMY01 to Streptomyces odonnellii (98.57%). All of isolates had morphological characteristics as the genus Streptomyces bacteria. The highest Plasmodium inhibition (81.84 ± 3.5%) was demonstrated by ethyl acetate extract of marine-derived Streptomyces sp. GMY01 (12.5 µg/mL). Non-ribosomal polyketide synthetase (NRPS), polyketide synthase (PKS) and hybrid of NRPS-PKS were the major BGCs in all Streptomyces. Majority of the Streptomyces produced compounds containing CHON elements with molecular weight approximately 100-400 Da. The active extract of GMY01 bacterium had five major detected compounds, namely kuraramine (C12H18N2O2), laminine (C9H20N2O2) 2-ethylacetanilide (C10H13NO), propoxur (C11H15NO3), and 3-methyl-1,2-diphenylbutan-1-one (C17H18O). This Indonesian marine bacterium is potential for bioassay guided isolation of antiplasmodial compounds in the future studies.